Pendampingan Pengembangan Usaha Kicimpring Dua Putra - Kurniawan, Edbert; Jennifer, Thio; Sugiharto, Phoebe Aurelia; Gunawan, Erick Nathanel; Revanza, Figo; Farres, Syahreza Nurirly; Jonathan, Alfred; Ludji, Theodorus Radja (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2025)
Kicimpring brand Dua Putra is a snack food MSME (Micro, Small, and Medium Enterprise) originating from Sindangjawa Village that sells kicimpring. The problem encountered at Dua Putra is the lack of certification for the household food industry, which results in suboptimal distribution. Additionally, there are errors in the writing on the packaging label, which could lead to violations of statutory regulations. Furthermore, the partners experience a shortage of raw materials and lack structured financial records to help measure sales. The aim of the prepared program is to address these partner issues and also elevate the class of Dua Putra MSMEs. Through this activity, the accompanying team succeeded in addressing the main problems and increasing the efficiency of the work program, from marketing and operational perspectives to financial aspects.